THEORETICAL AND LEGAL ASPECT OF CYBER VIOLENCE: NOTION AND CONTENT - Новіков, Микола Михайлович; Новікова, Марія Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
The purpose of the theses is to analyze some aspects of the cyber violence, which has theoretical, legal and applied character. The main tools of such violence are finding and using computer technics, cybernetic (general and local) computer net by a circle of persons during a certain period of time, in some space and inflicting other people psychically, biologically, physically, economically, financially; property and weapons are involved as well. The methods of research are general scientific and special methods of scientific cognition, including the dialectical method, methods of formal logic, structural-logical method, categorical, etc. Results: it is determined that overcoming cyber violence in Ukraine requires the formation of a system of comprehensive measures. First of all, it concerns the creation of an appropriate mechanism of legal regulation, which will clearly define the legal status of bodies and units that will deal with the issue of combating cyberbullying. Discussion: the cyber violence is known to suppress its victims’ consciousness and will by those people having an active motivation and socially dangerous or deviant behavior. Such behavior destabilizes the society and state as well and general human values (a human being with his or her rights and freedoms; a modern state and law; civil society and democracy; mechanisms of state power regarding its centralization and decentralization with the division of the latter into tree branches etc) are getting ruined. The most of cyber violence cases are known to take place among young people with the low level of social morality and culture and legal knowledge as well. In such a society, it is difficult to find offenders mocking those who are weaker than they. According to the more true data of the UNICEF, 50% of teenagers in Ukraine were victims of such violence. The statistical analysis of the cyber violence among the Ukrainian adults is unknown or latent because the form of psychological persecution is hidden in the mobile nets like Instagram, Telegram etc.